Chromodomain Helicase DNA-Binding Protein 7 Is Suppressed in the Perinecrotic/Ischemic Microenvironment and Is a Novel Regulator of Glioblastoma Angiogenesis. (24th January 2019) - Boyd, Nathaniel H.; Walker, Kiera; Ayokanmbi, Adetokunbo; Gordon, Emily R.; Whetsel, Julia; Smith, Cynthia M.; Sanchez, Richard G.; Lubin, Farah D.; Chakraborty, Asmi; Tran, Anh Nhat; Herting, Cameron; Hambardzumyan, Dolores; et al.
Abstract : Tumorigenic and non-neoplastic tissue injury occurs via the ischemic microenvironment defined by low oxygen, pH, and nutrients due to blood supply malfunction. Ischemic conditions exist within regions of pseudopalisading necrosis, a pathological hallmark of glioblastoma (GBM), the most common primary malignant brain tumor in adults. To recapitulate the physiologic microenvironment found in GBM tumors and tissue injury, we developed an in vitro ischemic model and identified chromodomain helicase DNA-binding protein 7 (CHD7) as a novel ischemia-regulated gene. Point mutations in the CHD7 gene are causal in CHARGE syndrome (a developmental disorder causing coloboma, heart defects, atresia choanae, retardation of growth, and genital and ear anomalies) and interrupt the epigenetic functions of CHD7 in regulating neural stem cell maintenance and development. Using our ischemic system, we observed microenvironment-mediated decreases in CHD7 expression in brain tumor-initiating cells and neural stem cells. Validating our approach, CHD7 was suppressed in the perinecrotic niche of GBM patient and xenograft sections, and an interrogation of patient gene expression datasets determined correlations of low CHD7 with increasing glioma grade and worse patient outcomes. Segregation of GBM by molecular subtype revealed a novel observation that CHD7 expression is elevated in proneural versus mesenchymal GBM. Genetic targeting of CHD7 and subsequent gene ontology analysis of RNA sequencing data indicated angiogenesis as a primary biological function affected by CHD7 expression changes. We validated this finding in tube-formation assays and vessel formation in orthotopic GBM models. Together, our data provide further understanding of molecular responses to ischemia and a novel function of CHD7 in regulating angiogenesis in both neoplastic and non-neoplastic systems. Stem Cells   2019;37:453–462 : Abstract : The ischemic microenvironment in both tumor and non-neoplastic tissue can drive new blood vessel formation to adapt to changes in pH, oxygen tension, and restricted nutrient availability. Using neural progenitor and glioblastoma cells in an in vitro ischemic model, we demonstrated that mRNA and protein expression of the epigenetic reader chromodomain helicase DNA-binding protein 7 was suppressed in the ischemic microenvironment. Reducing chromodomain helicase DNA-binding protein 7 altered the transcriptome to increase angiogenesis-related pathways that include CHI3L1 (YKL-40) and increased measures of angiogenesis in vitro and in vivo.